What is a tilt table test and why is it performed during the investigation of syncope?. (2nd October 2021) - White, Laura; Jones, Howell T; Davies, Anne
Abstract : Falls are one of the most common reasons for patients to present to the emergency department. Syncope is a common cause of falls, which disproportionately affects older people. In most cases, syncope can be confirmed with a detailed history and simple bedside tests, but tilt table testing remains an invaluable diagnostic adjunct in more complex cases. Often misunderstood, the tilt table test is a useful way to reproduce a patient's symptoms in a safe and controlled environment. The tilt table test is considered positive if the patient experiences symptoms associated with a drop in blood pressure or postural tachycardia. The test can support a diagnosis and can direct therapeutic interventions.